PERENCANAAN MANAJEMEN STRATEGIS DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI (Studi Kasus pada KRL Commuter Line Bogor-Jakarta). - Raymundus I Wayan Ray (Universitas Bunda Mulia, 2019)
The purpose of this research is to know and analyze employee performance at PT Kereta Api Indonesia (Persero) Bogor-Jakarta. Variables used to measure employee performance arestrategic planning management variables and job satisfaction. The population of this study is all employees at PT Kereta Api Indonesia (Persero) Bogor-Jakarta which pledges ± 550 people. The research data is derived from the results of the questionnaire distribution directly. Questionnaires distributed to employees as many as 55 people using accidental sampling technique. Data management in this research using method with quantitative approach. Data analysis technique used is multiple linear regression analysis calculated using SPSS program aid. The result of the research shows that (1) strategic management planning has a positive and significant effect on employee performance at PT Kereta Api Indonesia (Persero) Bogor-Jakarta. (2) Job satisfaction has a positive and significant effect on employee performance at PT Kereta Api Indonesia Persero) Bogor- Jakarta. (3) strategic management planning and job satisfaction simultaneously have a positive and significant effect on employee performance at PT Kereta Api Indonesia (Persero) Bogor-Jakarta. Keywords: Strategic Management Planning, Job Satisfaction, Employee Performance